“A Cross-sectional study of dyslipidemia among underweight, normal weight and overweight type 1 diabetic paediatric & adolescent patients coming to a tertiary care referral hospital, Mysuru, Karnataka”. - Kumar , Santhosh; Premnath, Devika (Student’s Journal of Health Research Africa, 2025)
Introduction The prevalence and impact of dyslipidemia in relation to body mass index (BMI) categories in T1DM patients remains a critical area of research. This study aims to evaluate the prevalence of dyslipidemia among underweight, normal weight, and overweight pediatric and adolescent T1DM patients and explore the effect of BMI on the prevalence of dyslipidemia. Materials and Methods This cross-sectional observational study included 58 pediatric and adolescent patients diagnosed with T1DM. The patients were classified into three BMI categories: underweight, normal weight, and overweight. Data were analyzed to assess the association between BMI categories and the prevalence of dyslipidemia. Results Dyslipidemia was observed in 82.76% of the participants, with the majority being classified as overweight (68.75%). A smaller proportion had a normal BMI (27.08%), while 4.17% were underweight. No significant association was found between BMI categories and dyslipidemia (p = 0.4735). The study also noted that the mean age of participants was 10.19 ± 4.96 years. Conclusion The study highlights the high prevalence of dyslipidemia among pediatric and adolescent T1DM patients, particularly those who are overweight. While no significant association between BMI categories and dyslipidemia was found, these findings suggest the importance of monitoring lipid profiles in T1DM patients, especially those with higher BMI, to mitigate the risk of cardiovascular complications. Recommendations Given the rising prevalence of overweight and obesity among pediatric and adolescent T1DM patients, understanding the impact of BMI on dyslipidemia is of critical importance. Identifying BMI-related lipid abnormalities can facilitate early intervention strategies, including lifestyle modifications, dietary interventions, and tailored insulin regimens to mitigate cardiovascular risk. Furthermore, the findings of this study could contribute to the development of targeted screening guidelines for dyslipidemia in pediatric T1DM populations, optimizing long-term metabolic health outcomes.